A STUDY ON THE CONTAMINATION OF KHABUR RIVER WITH HEAVY METALS DUE TO SPATIAL AND SEASONAL DISCHARGED WASTEWATER IN THE IRAQI KURDISTAN REGION: Heavy Metals - Hussain , Gulistan A.; Umer, Mustafa I.; Ahmed , Musher R. (Science Journal of University of Zakho, 2023)
The main objective of the present study is to spatially evaluate the water contamination of Khabur River, before it arrives in Zakho City, inside the city, and after it leaves the city of Zakho by heavy metals. Also, the seasonal effects of Zakho municipal wastewater discharged in the Khabur River were detected in this study. The results showed that some heavy metals, such as Ni, were not detected in all studied samples in this study due to their low concentration levels. It is indicated that heavy metals are statistically affected by spatial location and high amounts were detected after leaving, compared to before entering the city which indicates that municipal wastewater is the main source of metal pollution. However, all water tests met the WHO’s authorized limits. The average detected concentrations of copper, iron, manganese, and lead ranges from 0.003 to 0.025 mg/L, 0.000 to 0.054 mg/L, and 0.057 to 0.112 mg/L, and 0.014 to 0.135 mg/L respectively, while the highest concentrations of copper and iron were recorded significantly in Bedare (0.025 mg/L, 0.054 mg/L) respectively. The highest concentration of Lead (Pb) was detected in Chamtre and Tawke 0.117 mg/L and 0.135 mg/L respectively and this increase may be due to the presence of oil in the discharged industrial wastewater, in this village. Regarding season’s effects, higher mean concentrations for Mn 0.13423 mg/L, Fe, and 0.04208 mg/L were recorded in the autumn season. However, copper and lead had higher mean concertation 0.02389 mg/L, and 0.097 mg/L respectively, during the winter season, while the lowest mean concentration of copper was recorded in autumn, and lead in the summer season had a minimum concentration. There was a significant difference (P <0.01) in the seasonal variation of Cu, Fe, Mn, and Pb (P=0.001).